Immunohistochemical expression of ICAM-1 and Cortactin as cell adhesive molecule and invasive markers in Hodgkin’s and non-Hodgkin’s lymphoma of the head and neck region (A comparative study) - Kasim, Zaydoon M; Younis, Wasan H (Journal of Baghdad College of Dentistry, 2014)
Background: Lymphomas are a group of diseases caused by malignant lymphocytes that accumulate in lymph nodes and cause the characteristic clinical features of lymphadenopathy. Intercellular adhesion molecule-1 (ICAM-1) (CD54) is a transmembrane glycoprotein belonging to the immunoglobulin superfamily of adhesion molecules. Cortactin was first identified as one of the major substrates for src kinase. because it localized to Cortical actin structures, The aims of this study was to evaluate and compare the immunohistochemical of ICAM-1 expression as cell adhesion molecule marker and Cortactin expression as invasive marker. Material and Methods: This study was performed on (68) formalin-fixed, paraffin-embedded blocks, histopathologically diagnosed as lymphoma (head and neck lesions).Immunohistochemical staining of ICAM-1and Cortactin was performed on each case of the study sample. Results: The expression of ICAM-1 was membranous and cytoplasmic, the study cases showed a 98.5% positive reaction to ICAM-1, score 2 was the most common and found in 69.1% of all cases.The expression of Cortactin was cytoplasmic, 98.5% of cases expressed positive reactions to Cortactin, score 1 was the most common and found in 42.7% of all cases. Conclusion: Although the two markers showed a higher expression rate in all lymphomas (both HL and NHL) in this study, they can't be used to differentiate between them, nor can be used to differentiate between the subtypes of both HL and NHL. The high ICAM-1positive expression clarified that in addition to its role in cell-cell and cell-stromal interactions, it participates in proliferation, differentiation and invasion of malignant lymphoma cells.The present study is the first one that used Cortactin as an invasive marker for lymphoma.